2013
DOI: 10.1177/1933719112453509
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hypoxia Impairs Cytochrome Oxidase Activity Via Oxidative Stress in Selected Fetal Guinea Pig Organs

Abstract: We hypothesized that chronic hypoxia disrupts mitochondrial function via oxidative stress in fetal organs. Pregnant guinea pig sows were exposed to either normoxia or hypoxia (10.5% O2, 14 days) in the presence or absence of the antioxidant, N-acetylcysteine (NAC). Near-term anesthetized fetuses were delivered via hysterotomy, and fetal livers, hearts, lungs, and forebrains harvested. We quantified the effects of chronic hypoxia on cytochrome oxidase (CCO) activity and 2 factors known to regulate CCO activity:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 52 publications
(67 reference statements)
2
50
0
Order By: Relevance
“…In this study, antenatal maternal treatment with a glutathione precursor (NAC) was tested, in order to prevent the long‐lasting vascular effects of FGR. Previous studies using diverse models of FGR in guinea‐pigs have demonstrated that maternal treatment with NAC reduces markers of oxidative stress in different cardiovascular tissues . The present results showed that antenatal treatment with NAC was associated with a normal perinatal and post‐natal growth, and endothelial function.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, antenatal maternal treatment with a glutathione precursor (NAC) was tested, in order to prevent the long‐lasting vascular effects of FGR. Previous studies using diverse models of FGR in guinea‐pigs have demonstrated that maternal treatment with NAC reduces markers of oxidative stress in different cardiovascular tissues . The present results showed that antenatal treatment with NAC was associated with a normal perinatal and post‐natal growth, and endothelial function.…”
Section: Discussionsupporting
confidence: 70%
“…; Al‐Hasan et al . ). In contrast, in the present study, NAC treatment reverted the effect of an impaired utero‐placental perfusion on fetal growth restriction not only at the brain level but also by improving fetal weight as well as lower body organs (Table ).…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, only three studies have investigated the effects of developmental hypoxia on vertebrate mitochondrial respiration. In mammalian models of prenatal hypoxia, fetuses from pregnant dams exposed to 10% oxygen have lower rates of respiration, mitochondrial efficiency, and enzymatic activities of ETC complexes, and these effects are interpreted as pathological (4, 11). In contrast, the efficiency of ATP production is increased in neuronal mitochondria from chick embryos exposed to 13% oxygen, and this effect is heightened in native highland species (6).…”
Section: Discussionmentioning
confidence: 99%